Experiências, sensibilidades e práticas docentes: ensino de história e a memória das Ligas Camponesas em Sapé (2017-2022) - Lima, Paulo Roberto Francisco de (2023)
The related research aims to analyze the Teaching of Local History at the Luiz José Gonçalo Municipal School, located in the rural area of the city of Sapé in Paraíba, based on the historical knowledge brought by students to the classroom about the peasant struggles historically experienced in the city. The initial proposal is to focus on the contents of Local History incorporated into the school curriculum by municipal legislation, namely: the Peasant Leagues and the history of Sapé. These two contents gained visibility in Elementary School History classes by allowing students to tell in the classroom the stories heard at home and experienced by their parents and grandparents. Because it is a rural community, the feeling of struggle and resistance brought in the memory of the rural workers who crystallized the image of their union leaders as defenders of their rights is still strong. This knowledge was brought to the classroom from Oral History, making students actively participate in the production of didactic material that were used in the classroom to build historical learning. History classes became an opportunity for us to share and build knowledge together: the narrated stories served to produce the materials that were later discussed in the classroom, making students feel even more valued and protagonists in the construction of their own history. Theoretically, we dialogue with the categories of appropriation from Roger Chartier, to think about how these stories were appropriated by the school community, from experience from Jorge Larrosa, to think about how the subjects involved were affected and transformed, from sensibilities from Sandra Pesavento, to understand the emotions contained in stories told in the classroom and in didactic material from Circe Bittencourt, as being what allows the teacher to problematize knowledge in the classroom. Methodologically, we will work with the memories from the experiences narrated by the students, parents and guardians, supporting us in the writings of Walter Benjamin, which allows, from these narratives, to reflect and preserve the stories that were silenced by the official stories, reinforcing that the study of History Location in a school in the rural area of the city of Sapé is important to understand how the Teaching of History can be able to build a peasant identity of resistance.